Advances in research on the protective mechanisms of traditional Chinese medicine (TCM) in myocardial ischaemia-reperfusion injury. (31st December 2022) - Zhang, Jiexin; Hu, Yonghe; Wang, Han; Hou, Jun; Xiao, Wenjing; Wen, Xudong; Wang, Tingting; Long, Pan; Jiang, Hezhong; Wang, Zhanhao; Liu, Huawei; Chen, Xin
Abstract: Context: Developing effective drugs to treat myocardial ischaemia-reperfusion (MI/R) injury is imperative. Traditional Chinese medicines (TCMs) have had considerable success in the treatment of cardiovascular diseases. Elucidating the mechanisms by which TCMs improve MI/R injury can supplement the literature on MI/R prevention and treatment. Objective: To summarise TCMs and their main protective mechanisms against MI/R injury reported over the past 40 years. Methods: Relevant literature published between 1980 and 2020 in Chinese and English was retrieved from the Web of Science, PubMed, SpringerLink, PubMed Central, Scopus, and Chinese National Knowledge Infrastructure (CNKI) databases. Search terms included 'medicinal plants', 'myocardial ischaemia reperfusion injury', 'Chinese medicine prescriptions', 'mechanisms', 'prevention', 'treatment' and 'protection'. For inclusion in the analysis, medicinal plants had to be searchable in the China Medical Information Platform and Plant Database. Results: We found 71 medicinal species (from 40 families) that have been used to prevent MI/R injury, of which Compositae species (8 species) and Leguminosae species (7 species) made up the majority. Most of the effects associated with these plants are described as antioxidant and anti-inflammatory. Furthermore, we summarised 18 kinds of Chinese compound prescriptions, including the compound Danshen tablet and Baoxin pill, which mainly reduce oxidative stress and regulate mitochondrial energy metabolism. Discussion and conclusions: We summarised TCMs that protect against MI/R injury and their pharmacological mechanisms. This in-depth explanation of the roles of TCMs in MI/R injury protection provides a theoretical basis for the research and development of TCM-based treatment drugs.